2020
DOI: 10.1016/j.heliyon.2020.e03834
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness interventions reduce blood pressure in patients with non-communicable diseases: A systematic review and meta-analysis

Abstract: Mindfulness based interventions (MBIs) are an emerging area of empirical study, not only in positive psychology, but also in clinical health care. This research aims to synthesize the evidence about whether MBIs reduce blood pressure (BP) in patients with non-communicable diseases (NCDs). Methods: Relevant studies were identified via PubMed, the Cochrane Library, Embase and the CINAHL database between 2009 and 2019. The papers selected focused on mindfulness and the effect of these on the BP of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…In an article about nursing leaders, they are identified as playing an important role in retention of nurses, producing quality outcomes for staff nurses and patients, therefore affecting the whole health care environment (21). In a review about social and behavioral science to give support to COVID response, the authors mention the importance of leaders as representative members of the team (22). In FoCo, leaders practice with the team and this can be one of the explanations for its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In an article about nursing leaders, they are identified as playing an important role in retention of nurses, producing quality outcomes for staff nurses and patients, therefore affecting the whole health care environment (21). In a review about social and behavioral science to give support to COVID response, the authors mention the importance of leaders as representative members of the team (22). In FoCo, leaders practice with the team and this can be one of the explanations for its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“… 43 A systematic review among people with non-communicable diseases found systolic BP was reduced after the eight-week MBSR (−6.90 mmHg [95% CI: −10.82, −2.97]), followed by the 12-week breathing awareness meditation (−4.10 mmHg [95% CI: −7.54, −0.66]), and eight-week mindfulness-based intervention (−2.69 mmHg [95% CI: −3.90, −1.49]) and diastolic BP was reduced after eight-week MBSR (−2.45 mmHg [95% CI: −3.74, −1.17]) and the eight-week MBI (−2.24 mmHg [95% CI: −3.22, −1.26]). 44 Another systematic review among patients with CVD in 2020 showed benefits on systolic BP ( d + = 0.89, 95% CI = 0.26, 1.51) and psychological symptoms ( d + s = 0.49–0.64), but not diastolic BP. 45 Another systematic review by Zou evaluated the effect of mindful exercises for patients after stroke showed significantly improvement on the sensorimotor function on lower limb (SDM = 0.79; 95% CI, 0.43–1.15; I 2 = 62.67%) and upper limb (SDM = 0.7; 95% CI, 0.39–1.01; I 2 = 32.36%).…”
Section: Effects On Physical Healthmentioning
confidence: 99%
“…Mindfulness has an ample of benefits and generates well-being by reducing the levels of anxiety, depression and pain of individuals (Behan, 2020). A review study found that people with health conditions such as hypertension, diabetes, or cancer had a significant reduction in blood pressure when they practiced mindfulness-based stress reduction (Intarakamhang, et al, 2020). Brief mindfulness meditation improves mood, reduces fatigue and also improves visuo-spatial processing, working memory and executive functioning.…”
Section: Relationship Between Mindfulness and Well-beingmentioning
confidence: 99%